Analisa Hasil Penyusutan Kadar Air Temulawak Ditinjau Dari Waktu Pengeringan - Mochamad Chanifuddin Najib, Retno Eka Pramitasari (Reaktom : Rekayasa Keteknikan dan Optimasi, 2021)
Temulawak is a plant that is included in the category of plants that are very good for health. In its management, the community still uses natural methods such as solar heat, even though this method is less effective because the weather in Indonesia is uncertain. Therefore, there must be a new solution, one of which is to use oven drying. Oven drying is one method of drying using a temperature variation of 60Â°C with a time variation of 120 minutes. From the results of this study, the shrinkage value of the initial weight of the material was 400grams after the drying process was carried out, the final weight was 239.6 grams or the shrinkage was 40%. From this it can be concluded that the temperature and drying time are very influential for reducing the water content of temulawak.